Incremental cost per quality-adjusted life year gained? The need for alternative methods to evaluate medical interventions for ultra-rare disorders. (July 2014) - Schlander, Michael; Garattini, Silvio; Holm, Søren; Kolominsky-Rabas, Peter; Nord, Erik; Persson, Ulf; Postma, Maarten; Richardson, Jeff; Simoens, Steven; Solà Morales, Oriol de; Tolley, Keith; Toumi, Mondher
Drugs for ultra-rare disorders (URDs) rank prominently among the most expensive medicines on a cost-per-patient basis. Many of them do not meet conventional standards for cost–effectiveness. In light of the high fixed cost of R&D, this challenge is inversely related to the prevalence of URDs. The present paper sets out to explain the rationale underlying a recent expert consensus on these issues, recommending a more rigorous assessment of the clinical effectiveness of URDs, applying established standards of evidence-based medicine. This may include conditional approval and reimbursement policies, which should be combined with a firm expectation of proof of a minimum significant clinical benefit within a reasonable time. In contrast, current health economic evaluation paradigms fail to adequately reflect normative and empirical concerns (i.e., morally defensible 'social preferences') regarding healthcare resource allocation. Hence there is a strong need for alternative economic evaluation models for URDs.